Is Idiopathic Cuneate Gyrus Herniation an Isolated Variant or a Coexisting Finding in Pediatric Cases? An Magnetic Resonance Imaging Based Study - Hanife Gülden Düzkalır; Emine Çalışkan (Galenos Publishing House, 2024)
Objective: We aimed to investigate whether idiopathic cuneate gyrus herniation (ICH) is an anomaly or a normal variant, its prevalence, whether there is a coexisting finding or pathology, as well as to characterize it with magnetic resonance imaging (MRI) findings. Method: We evaluated 0-17-year-olds' brain MR images from January 2021-August 2023 at our clinic. Standard brain protocols utilize 1.5 Tesla MRI scanners. ICH and congenital brain abnormalities were evaluated in optimal brain MRIs. Malformations were classified as posterior fossa anomalies (PFA), commissural and cortical developmental anomalies (CCDA), and midline malformations. Results: Our study comprised 691 pediatric brain MRIs with a mean age of 5.93±3.4 years, with 48.77% male and 51.23% female. The mean age of 32 ICH (+) patients was 6.19±4.02 years, with 40.63% male and 59.37% female. The prevalence of ICH was 32/691 (4.6%). In 63 (9.11%) congenital brain malformation patients, ICH presence differed (p=0.005). Congenital brain malformation patients with ICH showed a significantly higher PFA rate (n=8) than without ICH. The frequency of CCDA (n=23) and the association of PFA and CCDA (n=12) were significantly higher in ICH patients with congenital brain malformation. The frequency of congenital brain malformation was higher in 32 ICH (+) patients, with a rate of 50% (p<0.001). Conclusion: We found that ICH is more frequent than reported and may be associated with congenital brain malformations. ICH must be differentiated from pathology to avoid unnecessary procedures. Congenital brain abnormalities may accompany ICH and should be carefully screened.